PERAN NEGARA DALAM MENGOPTIMALKAN ZAKAT DI INDONESIA - Herdianto, Ahmad Wahyu (Fakultas Syariah, 2011)
AbstrakZakat has strategic potential to be developed into an instrument of income distribution. In Indonesia, its potential is not professionally managed. This paper examines the reality of the optimization of zakat in Indonesia to know the development of its management, its practice management and its distribution as well as the role of the State using charity funds to alleviate poverty. In the matter of charity, maximizing both the state’s role as regulator to revise Act No. 38 of 1999 on Zakat Management, as a facilitator for the optimization of application management functions, the use of information technology in the management of alms and as a motivator for socialization, education, guidance, and conscious movement of zakat and the role of the state as a distributor to apply the model of equal distribution and eight channels growth for productive activities is very significant to note. Zakat memiliki potensi strategis untuk dikembangkan menjadi salah satu instrumen pemerataan pendapatan. Di Indonesia, potensi zakat belum dikelola secara profesional. Tulisan ini bermaksud mengkaji realita optimalisasi zakat di Indonesia untuk mengetahui perkembangan pengelolaan zakat, praktek pengelolaan dan penyaluran zakat, serta peranan negara menggunakan dana zakat untuk mengentaskan kemiskinan. Dalam persoalan zakat, maksimalisasi peran negara baik sebagai regulator untuk merevisi UU No 38 Tahun 1999 Tentang Pengelolaan Zakat, sebagai fasilitator untuk optimalisasi penerapan fungsi manajemen, penggunaan teknologi informasi di dalam pengelolaan zakat dan sebagai motivator untuk melakukan sosialisasi zakat, pendidikan, pembinaan, maupun gerakan sadar zakat serta peran negara sebagai distributor untuk menerapkan model pemerataan dan pertumbuhan delapan jalur untuk kegiatan produktif sangat signifikan untuk diperhatikan.Kata Kunci: Negara, Pengelolaan, Penyaluran, Dana Zakat.